2006
DOI: 10.1055/s-2006-942462
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3,3-Disubstituted Isoindolin-1-ones via Iodoamination of α-Substituted Secondary 2-Vinylbenzamides

Abstract: A new and simple method for the preparation of 3,3-disubstituted isoindolin-1-ones from a-substituted 2-bromostyrenes is described. Construction of the isoindolin-1-one skeleton was accomplished by treating a-substituted secondary 2-vinylbenzamides, easily obtainable from the reaction of a-substituted 2-lithiostyrenes with isocyanates, with iodine to afford 3-substituted 3-iodomethylisoindolin-1-ones.A number of synthetic methods for 3-substituted isoindolin-1-ones have been reported, 1 mainly on account of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 2 publications
1
8
1
Order By: Relevance
“…The reaction was complete at 08 in 1 h, and the precipitated product was collected. However, we found that the spectroscopic data (IR and 1 H-NMR) of this product were not identical to those of previously prepared 2,3-dihydro-3-methyl-2,3-diphenyl-1H-isoindol-1-one [1]. We determined the structure of this product to be (E)-1,3-dihydro-3-methyl-3-phenyl-1-(phenylimino)isobenzofuran (6a) on the basis of its spectroscopic data and elemental analysis (see Exper.…”
contrasting
confidence: 73%
See 4 more Smart Citations
“…The reaction was complete at 08 in 1 h, and the precipitated product was collected. However, we found that the spectroscopic data (IR and 1 H-NMR) of this product were not identical to those of previously prepared 2,3-dihydro-3-methyl-2,3-diphenyl-1H-isoindol-1-one [1]. We determined the structure of this product to be (E)-1,3-dihydro-3-methyl-3-phenyl-1-(phenylimino)isobenzofuran (6a) on the basis of its spectroscopic data and elemental analysis (see Exper.…”
contrasting
confidence: 73%
“…of HI in MeCN at room temperature to yield the desired 2,3-dihydro-3,3-dimethyl-2-phenyl-1H-isoindol-1-one (3a) in fair yield. The IR and 1 H-NMR spectra were identical to those reported in [1]. The use of less than 2 mol-equiv.…”
supporting
confidence: 67%
See 3 more Smart Citations